1999
DOI: 10.1021/je990171n
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of HFCs in Pentaerythritol Tetraalkyl Esters

Abstract: difluoroethane (HFC152a) in pentaerythritol tetranonanoate, pentaerythritol tetra-2-ethylbutanoate, and pentaerythritol tetra-2-ethylhexanoate have been measured at temperatures between 303 and 363 K and pressures between 0.07 and 2.1 MPa. Henry's constant and the activity coefficient for HFCs at infinite dilution were derived for measurements below 0.34 MPa. The measurements were made by an isochoric method with an uncertainty of <2% for Henry's constant and <3% at high pressure. Within the investigated tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
57
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 6 publications
5
57
0
Order By: Relevance
“…Similar results were obtained by Grebner, who found that both R‐134a and R‐125 showed mixed negative and positive deviations from Raoult's law in POE 32 oils, depending on the refrigerant mole fraction 28 . Also, Wahlström and Vamling reported that R‐32 in pentaerythritol tetraalkyl esters showed negative deviation from Raoult's law over a temperature range of 303.15–363.15 K 7 . The two distinct solubility behaviors demonstrate the complexity of these refrigerant/oil mixtures, thus molecular simulation studies should be performed to better understand the intermolecular interactions responsible for those solubility behaviors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were obtained by Grebner, who found that both R‐134a and R‐125 showed mixed negative and positive deviations from Raoult's law in POE 32 oils, depending on the refrigerant mole fraction 28 . Also, Wahlström and Vamling reported that R‐32 in pentaerythritol tetraalkyl esters showed negative deviation from Raoult's law over a temperature range of 303.15–363.15 K 7 . The two distinct solubility behaviors demonstrate the complexity of these refrigerant/oil mixtures, thus molecular simulation studies should be performed to better understand the intermolecular interactions responsible for those solubility behaviors.…”
Section: Resultsmentioning
confidence: 99%
“…While most of the studies in this field focus on the determination of thermodynamic and physical properties of pure HFC refrigerants, few studies are documented in the open literature on the phase behavior, thermodynamic, and transport properties of HFC/lubricant binary mixtures, namely at low temperatures. Wahlström and Vamling investigated the solubility of R‐134a, R‐32, and R‐125 in a linear chained pure component POE, that is, pentaerythritol tetrapentanoate ester (PEC5), at temperatures between 303.15 and 363.15 K, and pressures ranging from 0.07 to 2.1 MPa 7 . Among the HFCs studied, R‐134a was found to be the most soluble refrigerant in PEC5 oils followed by R‐125 and R‐32 at a given temperature and pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Few data are available on the thermophysical properties of the refrigerant + lubricant systems [1][2][3][4][5][6][7][8][9][10][11], and most of them refer to hydrofluorocarbons (HFC) and commercial oils. However, the structure and composition of the commercial oils is usually not defined, since they are mixtures of different components and additives, and this complicates the development of reliable thermodynamic models able to predict the behaviour of the lubricant + refrigerant mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the regression of these models requires a large number of experimental data to determine the dependence of the solubility on pressure, temperature, and molecular structure. Unfortunately, in the literature there is a lack of such information, except for few systematic works, as [1][2][3][4][5][6][7]. For this reason, our group is involved in a research program to provide experimental measurements and the development of a general predictive model focused on the phase behavior of lubricant + refrigerant blends, with particular attention to systems of POE precursors and CO 2 [8][9][10][11][12][13][14].…”
mentioning
confidence: 99%